2004
DOI: 10.1902/jop.2004.75.6.866
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Supported Root Ratio Estimation From Projected Length and Area Using Digital Radiographs

Abstract: The results of this study indicate that a reliable estimate of the ratio of root surface area supported by alveolar bone cannot be determined from linear or area data. However, when the marginal bone destruction exceeds 2 mm from the CEJ, area estimation does not show a significant difference in the supported region. As demonstrated in this study, root surface ratio estimation function could be an advantage of digital dental x-ray systems in which projected root area is readily observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 11 publications
0
7
0
1
Order By: Relevance
“…Traditionally, 2‐D radiographic images and histomorphometry have provided linear data to enable investigators to make quantitative measurements associated with alveolar bone affected by periodontitis or following regenerative therapy 16,17 . Although new technologies are available for 3‐D assessment of bone volume, in general, approaches still measure 2‐D images linearly after projection from 3‐D real structures 18,19 . These methods have limitations, such as the accuracy or the precision of measurements 20,21 .…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, 2‐D radiographic images and histomorphometry have provided linear data to enable investigators to make quantitative measurements associated with alveolar bone affected by periodontitis or following regenerative therapy 16,17 . Although new technologies are available for 3‐D assessment of bone volume, in general, approaches still measure 2‐D images linearly after projection from 3‐D real structures 18,19 . These methods have limitations, such as the accuracy or the precision of measurements 20,21 .…”
Section: Discussionmentioning
confidence: 99%
“…The RSA of a tooth with a single root was evaluated with clinical accuracy from the projection data7. However, another study concluded that a reliable appraisal of the RSA and BSH ratio could not be determined from 2D linear or area data8. The inconsistent outcomes may be due to different sample sizes, appliances, methodologies, or statistical analyses78.…”
Section: Discussionmentioning
confidence: 99%
“…The roots of human teeth present a tapered but also complex anatomic morphology (i.e., the radius at a cross-section varies when measured from the center of the root to the facial, lingual, mesial, or distal root surface at different corono-apical levels). Scholars have investigated the quantitative relationship between the amount of residual periodontal attachment and total root surface area of one tooth with regard to periodontium loss5678. However, the differentiated information regarding the percentage of maximal bone support evaluated using a 2D view compared with that using a 3D image remains limited.…”
mentioning
confidence: 99%
“…The root was divided into n parts, each part was supposed to be a cylinder, the height of the cylinder was h, and the diameter of the cylinder was d, so RSA = ∑πhd i = π∑hd i . If h was small enough, ∑hd i = S, and RSA = πS 16 . Then, the loss of RSA was estimated: ratio ðrÞ = RSA l /RSA i × 100% [15,16].…”
Section: Rsa Measurement and Alveolar Bonementioning
confidence: 99%